Prinsip Integration of Economic Development and Environmental Protection Sebagai Bagian Dari Hak Asasi Manusia - Clara Ignatia Tobing (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
In maintaining their survival, humans need the resources provided by nature. However, as the human population grows, the use of resources increases as well. There is one thing that is then forgotten by humans, that all human activities have an impact on the environment, directly or indirectly. Often humans, as resource users and never think about the impact of resource use and environmental exploitation, are increasingly excessive. Meanwhile, in the era of globalization, economic development and industrialization are often more important issues for developing countries. One of the principles in international law that can overcome problems between development, the environment and human rights is the principle of integration of environmental protection and economic development. This principle is one of the elements of sustainable development. This research then uses normative juridical legal research, namely legal research conducted using data and information as contained in the literature. The results of the study show the era link between the principles of integration of environmental protection and economic development with human rights.